RANCANG BANGUN PENGERING GABAH SISTEM UDARA VACUM UNTUK GABUNGAN KELOMPOK TANI (GAPOKTAN) SIDO RUKUN DI DESA SIDOMULYO KECAMATAN ADIMULYO KABUPATEN KEBUMEN - Syahid; Fatchun Hasim; Sidiq Syamsul Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2020)
Abstract The Sido Rukun Farmer Group Association (Gapoktan Sido Rukun) is a partner engaged in agriculture. These partners often experience problems, namely that the rice produced is easily crushed when milled due to incomplete drying of the grain so that the quality of the rice is not good and even the quantity of rice decreases in the rainy season. Another problem experienced by this Gapoktan is the drop in the price of unhulled rice during the harvest season, even though high operational costs, especially high fertilizer prices. The use of agricultural technology is still minimal and the marketing of agricultural products, especially rice, is still conventional and individual. The design of the grain dryer with a vacuum air system contributes to solving problems in the field of agricultural technology, namely with the Gapoktan partner grain dryer. The drying technology developed is drying with gas fuel and a blower to suck air in the drying tub which is equipped with engine temperature control so that it can adjust the temperature appropriately and the level of moisture and humidity levels in the air appropriately. The results of the trials conducted to dry 300 kg of grain took 7-8 hours and the grain moisture content was 12.5. The purpose of this Community Service is to contribute to solving problems in the field of agricultural technology, namely by using the grain dryer and the management and marketing problems of the farmer group partners' crops. The current drying technology being developed is drying with natural gas which is equipped with engine temperature control so that it can adjust the temperature properly and the level of moisture and humidity levels in the air appropriately. Problems in management and marketing as well as setting fertilizer prices and grain prices are proposed to form farmer cooperatives. The special targets of this Community Service are (1) manufacture of grain dryers; (2) Regulation of temperature and moisture content Abstrak Gabungan Kelompok tani Sido Rukun ( Gapoktan Sido Rukun) merupakan mitra yang berkecimpung di bidang pertanian. Mitra tersebut sering mengalami permasalahan yaitu beras yang dihasilkan mudah hancur pada saat digiling dikarenakan pengeringan gabah yang tidak sempurna sehingga kualitas beras tidak bagus dan bahkan juga kuantitas beras menurun di musim hujan.Permasalahan lain yang dialami Gapoktan ini yaitu merosotnya harga gabah pada saat panen raya padahal biaya operasional tinggi terutama harga pupuk yang tinggi.Pemanfaatan teknologi pertanian juga masih minim serta pemasaran hasil pertanian terutama padi masih konvensional dan individual. Rancang bangun pengering gabah dengan sistem udara vacum ini berkontribusi menyelesaikan permasalahan pada bidang teknologi pertanian yaitu dengan alat pengering gabah mitra Gapoktan tersebut. Teknologi pengeringan yang dikembangkan adalah pengeringan dengan bahan bakar gas dan blower untuk menyedot udara didalam bak pengeringan yang dilengkapi dengan pengontrolan suhu mesin sehingga bisa mengatur temperatur dengan tepat dan tingkat kadar air dan kelembaban udara dengan tepat. Hasil dari uji coba yang dilakukan untuk mnegringkan gabah 300 kg diperlukan waktu 7-8 jam dan kadar air gabah sebesar 12,5. Tujuan Pengabdian pada Masyarakat ini adalah berkontribusi menyelesaikan permasalahan pada bidang teknologi pertanian yaitu dengan alat pengering gabah dan masalah- masalah menejemen dan marketing hasil panen mitra Gapoktan tersebut. Teknologi pengeringan saat ini yang dikembangkan adalah pengeringan dengan bahan bakar gas yang dilengkapi dengan pengontrolan suhu mesin sehingga bisa mengatur temperatur dengan tepat dan tingkat kadar air dan kelembaban udara dengan tepat. Permasalahan di bidang menejemen dan pemasaran serta pengaturan harga pupuk dan harga gabah diusulkan membentuk koperasi petani.Target khusus Pengabdian PKM ini adalah (1) pembuatan pengering gabah; (2) Pengaturan suhu dan tingkat kadar air